Impulsivity and impulse control disorders in pregnancy. Issue 2 (3rd April 2018) - Eroğlu, Meliha Zengin; Şahan, Ebru
ABSTRACT: OBJECTIVE: We investigate the relationship between impulsivity and impulse control disorders (ICDs) in pregnancy. We claim that women with unplanned pregnancies are more impulsive and have a higher frequency of ICDs. METHODS: We perform a study on the 152 pregnant women who applied to Haydarpaşa Numune Training and Research Hospital Obstetrics outpatient clinic for routine follow-up. The participants are informed about the content of the study and their consents are taken. Socio-demographic characteristics of the participants are recorded. ICDs and impulsivity are assessed by Minnesota Impulse Control Disorders Interview Scale and Barrat Impulsivity Scale (BIS). RESULTS: ICD was present in 11.8% of the pregnant women ( n = 18) before gestation and 9.2% ( n = 14) during gestation. The motor and total impulsivity scores of those diagnosed with ICD during and before pregnancy were higher than those without ICD. The most common ICD during and before pregnancy was compulsive buying (3.3%). The relationship between pregnancy trimester and BIS score is insignificant. CONCLUSION: The motor and total impulsivity scores of those diagnosed with ICD before and during pregnancy were higher than scores of those not having ICD. It is well-known that ICDs cause not only pschiatric comorbidity but also illegal or high-risk behaviours, interpersonal, social, and economical problems. Thus, early recognition and treatment of ICDs in pregnancies will have a positive effect on both mothers' and babies' health.